Kemampuan Siswa Kelas X SMA Negeri 6 OKU Menulis Cerpen dalam Pembelajaran Bercerita Berpasangan - Awalludin, Awalludin; Nilawijaya, Rita; Contessa, Emilia; Lestari, Dewi (Bastrando: Jurnal Bahasa dan Sastra Indonesia, 2024)
The aim of this research is to describe the teaching and learning process of class X SMA Negeri 6 OKU students writing short stories in learning to tell stories in pairs and to explain the ability of class The method used in this research is descriptive method. Data collection techniques use observation techniques and test techniques. In making short stories using the learning technique of learning to tell stories in pairs. The results of the short story writing test in pair storytelling learning showed that of the 30 samples who got a score of 66 and above, there were 23 people (76.67%), 7 students who got a score of 65 or below (23.33%). Based on these results, it can be concluded that class X.2 students at SMA Negeri 6 OKU are able to write short stories in learning to tell stories in pairs. The advice for teachers is that they should always provide motivation to students, so that students are conditioned and happy to participate in learning. Students should take advantage of the opportunity given by the teacher to ask questions about learning material that is unclear and not yet understood, and increase their vocabulary. For researchers, with this research researchers can find out the abilities of class X.2 students at SMA Negeri 6 OKU. For other researchers, it is hoped that they can conduct research on writing short stories using different media, methods, and techniques in the future.